Stability of anthocyanin content and antioxidant capacity among local thai purple rice genotypes in different storage conditions - Supaporn Yamuangmorn (2018)
© 2018, Chiang Mai University. All rights reserved. This study determined whether storage conditions over six months affected grain anthocyanin content and antioxidant capacity of four purple rice genotypes with different initial anthocyanin content. Two forms of grain, paddy and brown rice were stored at three temperatures -25 °C, room temperature (25-30 °C) and 60 °C with three replications. In the two high-anthocyanin genotypes, the anthocyanin continued to decrease until the last month of storage, while the low-anthocyanin genotypes were not affected by storage time. Storage at 60 °C decreased the average anthocyanin content by 42%, compared to the 30% loss for grain stored at either -25 °C or room temperature. Brown rice retained more of its anthocyanin than paddy rice in the high anthocyanin genotypes. Antioxidant capacity substantially declined during storage in all genotypes and the capacity was higher in brown than paddy rice. There was a significant correlation between anthocyanin content and antioxidant capacity in the two high-anthocyanin genotypes, but not in the low-anthocyanin genotypes, indicating the possibility of different anti-oxidative key compounds between the low- and high-anthocyanin genotypes. These results suggest that the anthocyanin content and antioxidant capacity in purple rice genotypes would be most stable when stored at low temperature as brown rice.